Potassium Concentration on Admission Is an Independent Risk Factor for Target Lesion Revascularization in Acute Myocardial Infarction. (12th January 2014) - Honda, Tsuyoshi; Fujimoto, Kazuteru; Miyao, Yuji; Koga, Hidenobu; Ishii, Masanobu
Abstract : Background . Acute myocardial infarction (AMI) is accompanied by excessive production of catecholamines, which is characterized by a hypokalemic dip. A polymorphism of the adrenergic receptor has also been reported to be associated with target lesion revascularization (TLR) after coronary intervention. Subjects and Methods . We enrolled 276 consecutive patients with AMI within 24 hours of symptom onset, who underwent emergency coronary intervention using bare metal stents and had examinations over a 5–10-month follow-up period. The patients were divided into tertiles based on their serum potassium level on admission (low K, <3.9; mid K, ≥3.9, <4.3; and high K, ≥4.3). Results . Sixty-four TLRs were observed in the study. Increased potassium concentration was associated significantly with TLR. Patients in the high K group were about two and a half times more likely to have a TLR after AMI compared to those in the low K group. Multiple logistic analysis showed that potassium level on admission was an independent risk factor for TLR (odds ratio 1.69; confidence interval 1.04 to 2.74; P = 0.036 ). Conclusions . These findings indicated that increased potassium levels on admission might predict TLRs in AMI patients treated with bare metal stents.